Peptide Deformylase in Staphylococcus aureus: Resistance to Inhibition Is Mediated by Mutations in the Formyltransferase Gene - Margolis, Peter S. (American Society for Microbiology, 2000)
Peptide deformylase, a bacterial enzyme, represents a novel target for antibiotic discovery. Two deformylase homologs, defA and defB, were identified in Staphylococcus aureus. The defA homolog, located upstream of the transformylase gene, was identified by genomic analysis and was cloned from chromosomal DNA by PCR. A distinct homolog, defB, was cloned from an S. aureus genomic library by complementation of the arabinose-dependent phenotype of a P(BAD)-def Escherichia coli strain grown under arabinose-limiting conditions. Overexpression in E. coli of defB, but not defA, correlated to increased deformylase activity and decreased susceptibility to actinonin, a deformylase-specific inhibitor. The defB gene could not be disrupted in wild-type S. aureus, suggesting that this gene, which encodes a functional deformylase, is essential. In contrast, the defA gene could be inactivated; the function of this gene is unknown. Actinonin-resistant mutants grew slowly in vitro and did not show cross-resistance to other classes of antibiotics. When compared to the parent, an actinonin-resistant strain produced an attenuated infection in a murine abscess model, indicating that this strain also has a growth disadvantage in vivo. Sequence analysis of the actinonin-resistant mutants revealed that each harbors a loss-of-function mutation in the fmt gene. Susceptibility to actinonin was restored when the wild-type fmt gene was introduced into these mutant strains. An S. aureus Δfmt strain was also resistant to actinonin, suggesting that a functional deformylase activity is not required in a strain that lacks formyltransferase activity. Accordingly, the defB gene could be disrupted in an fmt mutant.